Recalls of tattoo and permanent makeup inks in the United States and a follow-up microbiological survey of inks with a previous recall history - Yoon, Sunghyun; Kondakala, Sandeep; Moon, Mi Sun; Huang, Mei-Chiung J.; Periz, Goran; Foley, Steven L.; Kweon, Ohgew; Kim, Seong-Jae (Frontiers in Public Health, 2023)
In this study, we collected voluntary recall records of tattoo and permanent makeup ink from the U.S. Food and Drug Administration (US FDA) Enforcement Report Database. The recall records contain information, such as recall date, manufacturer, ink color, reason for recall, and the microorganisms detected from the ink samples. Between 2003 and 2021, a total of 15 voluntary tattoo ink recalls occurred in the U.S. market, involving over 200 tattoo inks marketed by 13 manufacturers and one distributor. Fourteen recalls were due to microbial contamination, and one recall was due to allergic reaction. As follow-up, a microbiological survey of 28 tattoo inks of new batches from seven manufacturers having products that were previously recalled was conducted. Aerobic plate count (APC) and enrichment culture methods based on the FDA's Bacteriological Analytical Manual (BAM) were used to detect microbial contamination. The results revealed that six out of 28 tattoo inks were contaminated with bacteria and were produced by two manufacturers. The level of microbial contamination was less than 250 CFU/g in three of the tattoo inks and between 1×10 3 and 1×10 5 CFU/g in the other three inks. Eleven bacterial isolates were identified, including spore-forming Bacillus-related species and potentially pathogenic species. Overall, this study shows that some tattoo ink products produced by manufacturers with a recall history continue to be contaminated with microorganisms. This highlights the need for ongoing monitoring and quality control of such products.